Particle size dependent adsorption and reaction kinetics on reduced and partially oxidized Pd nanoparticles - Libuda, Jörg; et al. (Physical Chemistry Chemical Physics, 2007)
Combining scanning tunneling microscopy (STM), IR reflection absorption spectroscopy (IRAS) and molecular beam (MB) techniques, we have investigated particle size effects on a Pd/ Fe3O4 model catalyst. We focus on the particle size dependence of (i) CO adsorption, (ii) oxygen adsorption and (iii) Pd nanoparticle oxidation/ reduction. The model system, which is based on Pd nanoparticles supported on an ordered Fe3O4 film on Pt(111), is characterized in detail with respect to particle morphology, nucleation, growth and coalescence behavior of the Pd particles. Morphological changes upon stabilization by thermal treatment in oxygen atmosphere are also considered. The size of the Pd particles can be varied roughly between 1 and 100 nm. The growth and morphology of the Pd particles on the Fe3O4/ Pt(111) film were characterized by STM and IRAS of adsorbed CO as a probe molecule. It was found that very small Pd particles on Fe3O4 show a strongly modified adsorption behavior, characterized by atypically weak CO adsorption and a characteristic CO stretching frequency around 2130 cm(-1). This modification is attributed to a strong interaction with the support. Additionally, the kinetics of CO adsorption was studied by sticking coefficient experiments as a function of particle size. For small particles it is shown that the CO adsorption rate is significantly enhanced by the capture zone effect. The absolute size of the capture zone was quantified on the basis of the STM and sticking coefficient data. Finally, oxygen adsorption was studied by means of MB CO titration experiments. Pure chemisorption of oxygen is observed at 400 K, whereas at 500 K partial oxidation of the particles occurs. The oxidation behavior reveals strong kinetic hindrances to oxidation for larger particles, whereas facile oxidation and reduction are observed for smaller particles. For the latter, estimates point to the formation of oxide layers which, on average, are thicker than the surface oxides on corresponding single crystal surfaces.